Cropping season affect the performance of basil cultivars and hybrids - Jéssika Andreza Olveira Pinto; Arie Fitzgerald Blank; Thiago Matos Andrade; José Carlos Freitas de Sá Filho; Luís Fernando de Andrade Nascimento; Dennis Crystian Silva; Maria de Fátima Arrigoni-Blank (Bioscience Journal, 2018)
The objective of this work was to evaluate the performance of basil cultivars and hybrids in two cropping seasons. The experiments were conducted in a randomized block design, with three replications. Twenty-four basil genotypes were tested (20 commercial cultivars and four hybrids), in the dry season (oct.-dec./2015) and in the rainy season (apr.-jun./2016). The evaluated variables were: plant height (cm plant-1), canopy width (cm plant-1), leaf dry weight (g plant-1), and essential oil yield (mL plant-1). The data of each period were subject to analysis of variance and the means were grouped by the Scott-Knott test (pâ‰¤0.05). The individual and joint analyses of variance were performed for the experiments in both seasons. The estimated parameters were: coefficient of genetic variation (CVg), coefficient of environmental variation (CVe), CVg/CVe ratio, and heritability (h2). Leaf dry weight values per plant ranged from 6.23 to 75.00 g plant-1 (dry season) and from 9.17 to 31.34 g plant-1 (rainy season). The hybrid Cinnamon x Maria Bonita (1.50 mL plant-1) and the cultivar Mrs. Burns (1.44 mL plant-1) presented higher essential oil yield in the dry season. All the evaluated variables showed high heritability (h2) (> 50%) and CVg/CVe ratio (> 1.0), in both cropping seasons, indicating a favorable condition for selection. The cropping season influences the biomass and essential oil yield of basil.